18. yy. şairi Mustafa Fenni divan (inceleme-tenkitli metin-dizin) cilt: 1 - Demirkazık, Hacı İbrahim (My University, 2009)
This thesis has been prepared to include the life of Mustafa Fennî, who lived in the first half of the 18th century, his literary personality and style. This thesis has also been prepared to present a critical theory related to his work. The thesis which has been prepared using scientific methods handles this critical theory based on three editions of his only known work, Dîvân. This thesis is formed on three parts: In the first part, Fennî’s life has been enlightened within the light of the knowledge in the Dîvân and the historical sources. Later on, Fennî’s literary personality has been argued. Moreover, in this part the other poets who nicknamed Fennî have been studied. In the second part, Dîvân has been detected regarding to its form and theme. As titled “Form Qualifications” the elements of Dîvân’s verse form and types, rhyme and harmony have been evaluated. As titled “Theme Qualifications” the elements of religion, culture, society, nature and expression merit have been elaborated in the Dîvân. The third part has been included the critical text of the Dîvân and the concordance of the special names. With this PhD thesis Fennî’s life and his literary personality have been enlightened and his place in Turkish Literature has been tried to be put down. Therefore this study has been aimed to be a source book about 18th century-Classical Turkish Poem.

Bu çalışma, 18. yüzyılın ilk yarısında yaşamış olan Mustafa Fennî’nin hayatı ve edebî kişiliği, üslubu ve bilinen tek eseri olan Dîvân’ının tespit edilebilen üç nüshasından hareketle oluşturulan tenkitli metni ile bu metnin ilmî usüllerle incelenmesini içermektedir. Çalışma üç bölümden oluşmaktadır. Birinci bölümde Şairin Dîvân’ında yer alan bilgiler ile tarihî kaynaklarda bulunan bilgilerin ışığında Fennî’nin hayatı tespit edilmeye, ardından Fennî’nin edebî kişiliği ortaya konmaya çalışılmıştır. Ayrıca bu bölümde Fennî mahlaslı diğer şairler üzerinde de durulmuştur. İkinci bölümde çalışmaya konu olan Dîvân şekil ve muhteva yönünden tetkik edilmiştir. “Şekil Özellikleri” başlığı altında nazım şekil ve türleri, vezin, kafiye ve âhenk unsurları ele alınmış, “Muhteva Özellikleri” başlığı altında ise Dîvân’daki cemiyet, din, maddî kültür, tabiat ve söz varlığına dair unsurlar ayrıntılı bir biçimde incelenmiştir. Üçüncü bölüm ise Dîvân’ın tenkitli metni ve özel adlar dizininden oluşmaktadır. Hazırlanan bu doktora teziyle Fennî’nin hayatı ve edebî kişiliği ortaya konarak, Türk Edebiyatı içerisindeki yerinin tespit edilmesine çalışılmış, böylelikle 18. yüzyıl Klâsik Türk şiiri ile ilgili yapılacak inceleme ve değerlendirme çalışmalarına kaynak oluşturmak amaçlanmıştır.
Keywords: Divan Şiiri; Türk Dili